Progress in the study of typical planetary landforms over the past 30 years: a bibliometric analysis in CiteSpace - Zhang, Yutong; Cheng, Weiming (Frontiers in Astronomy and Space Sciences, 2025)
Landform investigation reports are fundamental datasets for ecology, geology, and geography as they record the morphological traces of planetary surface processes, which have been the focus of top journals and distinguished scholars. Investigating landforms on Earth and other planetary bodies is crucial for understanding planetary formation and geological evolution. Remote sensing techniques have proven to be powerful tools for studying terrestrial and planetary landforms, providing detailed insights into the interactions between land surfaces and both endogenic and exogenic forces and the mechanisms driving physical processes under different conditions. This study focuses on the remote sensing perspective of planetary landform investigations, highlighting recent progress in geomorphic research. Publications in top-tier journals over the last 30 years were selected for analysis. Our findings indicate that geological history and the environmental conditions conducive to the survival, growth, and daily activities of living organisms are of great concern. The United States, the European Union, China, Japan, and Canada, along with their aerospace research institutions, continue to be key research centers and play important roles all the time. Moreover, our literature survey reveals that research on planetary landforms is gaining momentum in more countries because of advancements in instrumentation and increased international collaboration. Celestial bodies that receive significant attention include planets, moons, and comets, while asteroids should receive more attention in the future. To advance our understanding of planetary landforms, higher-precision observation data and more refined simulations are essential. Continued improvements in international cooperation will be crucial for unraveling the complex geological histories within planetary landforms, contributing to our broader understanding of planetary evolution within the solar system.